2004
DOI: 10.1098/rstb.2003.1414
|View full text |Cite
|
Sign up to set email alerts
|

Virulence in malaria: an evolutionary viewpoint

Abstract: Malaria parasites cause much morbidity and mortality to their human hosts. From our evolutionary perspective, this is because virulence is positively associated with parasite transmission rate. Natural selection therefore drives virulence upwards, but only to the point where the cost to transmission caused by host death begins to outweigh the transmission benefits. In this review, we summarize data from the laboratory rodent malaria model, Plasmodium chabaudi, and field data on the human malaria parasite, P. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
212
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(224 citation statements)
references
References 269 publications
(394 reference statements)
12
212
0
Order By: Relevance
“…It is possible that the high levels of replication of normal FCV strains in large groups of cats such as rescue shelters may provide the required conditions necessary for the independent emergence of these hypervirulent strains. This is consistent with theories for the evolution of increased virulence in host populations with high levels of non-neutralising immunity [29,61]. Under these conditions, viral variants that are capable of replicating faster and to higher titres will be more likely to be transmitted and therefore positively selected for.…”
Section: Fcv-associated Virulent Systemic Diseasesupporting
confidence: 88%
“…It is possible that the high levels of replication of normal FCV strains in large groups of cats such as rescue shelters may provide the required conditions necessary for the independent emergence of these hypervirulent strains. This is consistent with theories for the evolution of increased virulence in host populations with high levels of non-neutralising immunity [29,61]. Under these conditions, viral variants that are capable of replicating faster and to higher titres will be more likely to be transmitted and therefore positively selected for.…”
Section: Fcv-associated Virulent Systemic Diseasesupporting
confidence: 88%
“…Whether or not similar effects occur in human co-infections with genetically diverse P. vivax strains remains unknown (Mackinnon & Read 2004). The increasing virulence of P. vivax strains, as demonstrated by numer- Porto et al 1992 ;b: Kolakovich et al 1996;c: Bruce et al 1999;d: Putaporntip et al 2000;e: Cui et al 2003;f: Bonilla et al 2006;g: Kim et al 2006;h: Prajapati et al 2006;i: Inwong et al 2007a;j: Inwong et al 2007b;k: Ferreira et al 2007;l: Gunasekera et al 2007; m: Karunaweera et al 2007; n: Joy et al 2008; CSP: circumsporozoite protein; GAM1: gametocyte antigen 1; MSP1: merozoite surface protein 1; MSP3α: merozoite surface protein 3α.…”
Section: Prevalence and Consequences Of Multiple-clone P Vivax Infecmentioning
confidence: 99%
“…Competition between co-infecting parasite clones for limited resources within a host is a major factor in the evolution of phenotypes such as virulence, transmissibility and drug resistance (Mackinnon & Read 2004). A series of elegant experiments with mice co-infected with different strains of Plasmodium chabaudi revealed that competition favours strains with higher virulence (de Roode et al 2005, Bell et al 2006, greater gametocyte production and increased transmissibility to mosquitoes (Taylor et al 1997, de Roode et al 2005.…”
Section: Prevalence and Consequences Of Multiple-clone P Vivax Infecmentioning
confidence: 99%
“…During this initial or acute phase of infection, different parasite strains reach different densities and cause varying degrees of anaemia and other pathology ( Field & Niven 1937;Field 1949;Kitchen 1949a;Molineaux et al 2001;Mackinnon & Read 2004). While most studies agree that specific immunity does not play a major role in this initial dynamics, there is considerable controversy over which factors drive the dynamics shortly after infection (Anderson et al 1989;Hellriegel 1992;Hetzel & Anderson 1996;McQueen & McKenzie 2004).…”
Section: Introductionmentioning
confidence: 99%